PS02.061: TRANILAST: SPECIFIC INHIBITOR OF TRPV2 IS THERAPEUTIC AGENT OF ESOPHAGEAL CANCER STEM CELLS. (14th September 2018) - Katsurahara, Keita; Shiozaki, Atsushi; Kudou, Michihiro; Shoda, Katsutoshi; Arita, Tomohiro; Konishi, Hirotaka; Morimura, Ryo; Murayama, Yasutoshi; Kuriu, Yoshiaki; Kubota, Takeshi; Ikoma, Hisashi; Nakanishi, Masayoshi; et al.
Abstract: Background: Recent studies revealed that membrane proteins, such as ion transporters, are specifically activated in cancer stem cells (CSCs). Therefore, these molecules are receiving a great attention as new chemotherapeutic targets of malignant tumor. This study aimed to investigate the expression and activity of ion transport-related molecules in CSCs of esophageal squamous cell carcinoma (ESCC). Methods: We sorted cells with high expression of ALDH1A1 via FACS, and then, CSCs were generated using the sphere formation assay. The gene expression profiles of CSCs were examined using a microarray analysis. Candidate genes of membrane proteins activated in CSCs were selected based on that microarray data. Anticancer effects induced by inhibition of the selected proteins were examined. Results: ALDH1A1 mRNA and protein levels were certainly upregulated in CSCs compared with non-CSCs. Obtained CSCs were resistant to Cisplatin and had the ability of re-differentiation. The results of the microarray analysis revealed that expressions of 50 genes of plasma membrane proteins were changed in CSCs, and that several genes related to ion channels, including transient receptor potential cation channel subfamily V member 2 (TRPV2), were upregulated. The upregulation of TRPV2 mRNA were also validated in CSCs derived from two types of esophageal cancer cell lines using RT-PCR method. Tranilast, which is specific TRPV2 inhibitor, was more cytotoxic at lower concentration in CSCs than in non-CSCs, and effectively decreased the number of tumorspheres. Further, Tranilast significantly decreased the cell population with high ALDH1A1 expression in esophageal cancer cells. Conclusion: The results of the present study suggest that TRPV2 is involved in the maintenance of CSCs, and Tranilast, which is specific inhibitor of TRPV2, becomes a promising targeted therapeutic agent against ESCC. Disclosure: All authors have declared no conflicts of interest.